2017
DOI: 10.1021/acsami.7b13941
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ag3PO4 Crystals with Tunable Shapes for Facet-Dependent Optical Property, Photocatalytic Activity, and Electrical Conductivity Examinations

Abstract: This work has developed conditions for the synthesis of AgPO cubes, rhombic dodecahedra, {100}-truncated rhombic dodecahedra, tetrahedra, and tetrapods by tuning the amount of NHNO, NaOH, AgNO, and KHPO solutions added. Use of a minimal amount of AgNO solution can form much smaller rhombic dodecahedra and tetrahedra. Submicrometer-sized AgPO cubes and rhombic dodecahedra with sizes larger than 300 nm do not exhibit the optical size effect, but ∼290 nm rhombic dodecahedra show a smaller band gap value than larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
104
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 31 publications
(81 reference statements)
4
104
0
Order By: Relevance
“…This result agrees with the results of Hsieh et al. that the highest barrier for electron transport exists on the (111) crystal facet of the Ag 3 PO 4 tetrahedron, leading to faster charge recombination than that of the cube …”
Section: Figuresupporting
confidence: 93%
See 1 more Smart Citation
“…This result agrees with the results of Hsieh et al. that the highest barrier for electron transport exists on the (111) crystal facet of the Ag 3 PO 4 tetrahedron, leading to faster charge recombination than that of the cube …”
Section: Figuresupporting
confidence: 93%
“…recently reported that the Ag 3 PO 4 tetrahedron was nearly inert for dye degradation, whereas the Ag 3 PO 4 cube generated the largest amount of hydroxyl radical ( . OH) . Thus, there has been no consensus on which crystal structure of Ag 3 PO 4 is advantageous as a photocatalyst.…”
Section: Figurementioning
confidence: 99%
“…For example, the same Cu 2 O particle can simultaneously behave like a metal, a semiconductor, and an insulator depending on the measured crystal facets, thereby changing our understanding of semiconductor behavior. Despite the poor electrical‐conductivity responses due to the large energy band gaps of Ag 3 PO 4 , Ag 3 PO 4 crystals still show slight face‐specific electrical‐conductivity differences . Density functional theory (DFT) calculations performed on Cu 2 O, Ag 2 O, and PbS have revealed distinctly different band structures and density‐of‐states (DOS) plots within a few (100), (110), and (111) surface planes, which can be very insightful to understanding the observed electrical‐conductivity differences .…”
Section: Introductionmentioning
confidence: 98%
“…Acetic acid was introduced to further tune the ZnS crystal growth rate to achieve particle size control. Previously, a similar strategy to lower the equilibrium toward crystal formation by a precipitation reaction was employed to make Ag 2 O, PbS, and Ag 3 PO 4 crystals with shape control …”
Section: Resultsmentioning
confidence: 99%